Disaster-FD: A Failure Detector for Disaster-Prone Environments - Silva, Abadio de Paulo; Rossetto, Anubis Graciela de M.; Sens, Pierre; Arantes, Luciana; Pasquini, Rafael; Coelho, Paulo (Anais do Latin-American Symposium on Dependable Computing (LADC); 2024: Anais do XIII Latin-American Symposium on Dependable Computing, 2024)
This paper introduces Disaster-FD, a failure detector designed for disaster-prone environments, focusing on real-time IoT network monitoring. Inspired by Impact-FD, Disaster-FD features active and federated monitoring to ensure network reliability under adverse conditions. Tested on the IoT-LAB platform, Disaster-FD demonstrates robust performance, enhancing IoT network resilience during disasters. It assesses reliability thresholds, confidence levels, and impact factors, ensuring efficient energy consumption and maintaining high network trust. This paper details Disaster-FD’s implementation, performance metrics, and experimental results, highlighting its potential for effective support in disaster management.